2023
DOI: 10.1098/rsob.220302
|View full text |Cite
|
Sign up to set email alerts
|

Spatial transcriptomes and microbiota reveal immune mechanism that respond to pathogen infection in the posterior intestine ofSebastes schlegelii

Abstract: The intestine is a site of immune cell priming at birth. Therefore, spatial transcriptomes were performed to define how the transcriptomic landscape was spatially organized in the posterior intestine of Sebastes schlegelii following Edwardsiella piscicida infection. In the healthy condition, we identified a previously unappreciated molecular regionalization of the posterior intestine. Following bacterial infection, most immune-related genes were identified in muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
0
0
0
Order By: Relevance
“…S. schlegelii , a demersal fish widely distributed in the northwest Pacific along the coast of China, Japan and the Korean Peninsula [ 14 ], has been extensively studied with a focus on its growth, behavior, physiology, immunity, and population genetics [ [15] , [16] , [17] , [18] ]. It has been reported that bacterial and viral pathogens threatened the yield of S. schlegelii .…”
Section: Discussionmentioning
confidence: 99%
“…S. schlegelii , a demersal fish widely distributed in the northwest Pacific along the coast of China, Japan and the Korean Peninsula [ 14 ], has been extensively studied with a focus on its growth, behavior, physiology, immunity, and population genetics [ [15] , [16] , [17] , [18] ]. It has been reported that bacterial and viral pathogens threatened the yield of S. schlegelii .…”
Section: Discussionmentioning
confidence: 99%